Integration of AI Voice-Based Micro-Learning to Enhance Elementary School Students’ Reading Comprehension - Mahayuni Mahayuni; Adam Mudinillah; Adam Idris (Yayasan Adra Karima Hubbi, 2025)
The integration of voice-based Artificial Intelligence (AI) micro-learning represents a promising innovation in elementary students’ reading instruction. This study aims to develop and examine the effectiveness of integrating voice-based AI micro-learning through a hybrid approach in enhancing elementary school students’ reading comprehension. The hybrid approach is employed to combine the strengths of AI and teachers in the learning process, enabling students to learn more effectively and efficiently. In this study, AI delivers instructional materials and provides feedback to students, while teachers monitor students’ progress and deliver appropriate interventions. The findings indicate that the integration of voice-based AI micro-learning through a hybrid approach significantly improves elementary school students’ reading comprehension. The study also reveals that students who engage with voice-based AI micro-learning within a hybrid approach demonstrate higher learning motivation and better reading abilities than those who rely on conventional instructional methods. This research is expected to contribute to the development of more effective and efficient reading instruction and to support the improvement of educational quality in Indonesia.